Analysis of harmonic oscillator mass parameters influence on multiband gap widening for Drude model acoustic metamaterial. Issue 3 (April 2021) - Shi, Huijie; Gao, Ming; Yin, Song; Wu, Shujiang
Abstract: Acoustic metamaterial is a kind of special microstructure of man-made composite material with vibration attenuation band gap. In view of the band gap widening methods, the Drude model with additional double harmonic oscillators five periodic spring-mass system is established, and then the steady-state displacement and velocity of each oscillator under different external excitation frequencies were calculated, the vibration transmission characteristic of the system is obtained. The band gap widening method is analyzed. The results show that, compared with the Drude model, a new high frequency band gap is developed by adding double harmonic oscillators, and with the increase of the additional oscillator mass, the total bandwidth of low frequency band gap is widen. The research provides theoretical basis and application basis to the design of vibration isolation structure implement specific frequency band of noise reduction.